KEMAMPUAN MAHASISWA STBA-PIA SEMESTER VIII T.A. 2021/2022 DALAM MENGGUNAKAN KATA KETERANGAN MODALITAS â€œXINGKUIâ€ DAN â€œXINGHAOâ€ - Hualangi, Cynthia; -, Vincent (Linguistik : Jurnal Bahasa dan Sastra, 2023)
This research is to determine the ability of STBA-PIA students in the VIII semester of the 2021/2022 academic year in using the adverb of modality â€œXingkuiâ€ and â€œXinghaoâ€ and explaining the factors that influence this ability. The research uses an integrative research design, quantitative descriptive research methods are combined with qualitative research methods. The sampling technique used the Cluster Random Sampling technique, namely 45 STBA-PIA students in the VIII semester of theÂ  2021/2022 academic year and the research subjects used the Purposive Sampling technique, 3 students from the upper group (top grades) and 3 students from the lower group (lowest grades). The data collection techniques used were tests and interviews. The results of data analysis show that the ability of VIII semester students is classified as very low with an average score of 58. The score that appears most often (mode) is 60, the middle score (median) is 60 and the standard deviation is 14. In addition, there is 1 person ( 2.2%) were categorized as very high, there were 3 people (6.7%) who were categorized as high, there were 7 people (15.6%) who were categorized as moderate, there were 15 people (33.3%) who were categorized as low and there were 19 people (42.2%) were categorized as very low. The factors that influence the abilities of STBA-PIA students are motivation factors, formal presentation factors and environmental factors (formal environment).Â Â